Effectiveness of the Instagram Media @Zonakalakkaro.Id_New in Meeting the Information Needs of the Karo People - Rakhas Djuniardi; Anang Anas Azhar; Abdullah Abdullah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The research problem addresses the effectiveness of the Instagram account @zonakalakkaro.id_new in meeting the information needs of the Karo ethnic group, as well as disseminating digital cultural information and local news. This study aims to analyze the effectiveness of @zonakalakkaro.id_new in fulfilling the information needs of the Karo people and to identify the most frequently sought-after information. Using a qualitative descriptive method with a case study approach, data were gathered through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The results indicate that the Instagram account @zonakalakkaro.id_new effectively meets the information needs of the Karo people in Karo Regency. The most highly sought-after information includes traffic conditions, accidents, crime, local culture, and regional tourism promotion. Fast, relevant, engaging, and easy-to-understand content presentation increases public trust in the account as a primary source of information. Beyond delivering breaking news, this account also functions as a cultural education medium that strengthens the identity of the Karo people. The younger generation utilizes this account due to its easy accessibility via social media, thereby supporting information dissemination, cultural preservation, and fostering sustainable community relations. Conclusion: The Instagram account @zonakalakkaro.id_new is effective in meeting the information needs of the Karo people while strengthening cultural education, local identity, and public trust. This research contributes to the development of digital communication and the preservation of Karo culture, serving as a reference for managing social media based on local community needs.